Formulasi Sirup Analgesik Ekstrak Etanol Daun Songgolangit (Tridax procumbens L.) - Tompunu, Citra; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2013)
ABSTRACT The aims of this research were to testing the quality of songgolangit leaves ethanol extract analgesic syrup. Songgolangit leaves ethanol extract analgesic syrup were make with 3 various concentrations of active substances which are 40%, 50%, 60% and the quality were testing. The outcome of quality testing of songgolangit leaves ethanol extract syrup has a good homogeneity. On organoleptic test, songgolangit leaves ethanol extract syrup was smelling like extract, has a bitter taste, and colored yellow. The pH of songgolangit leaves ethanol extract syrup be on the maximum stability which are on 5-7 pH. The average of castings time be on the similliar values with the positif control that become a parameter. Key words : analgesic, Tridax procumbens L.